2013
DOI: 10.1021/jp402298y
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spectra of the Protonated Indole Chromophore in the Gas Phase

Abstract: The electronic spectroscopy of cold protonated indole was investigated experimentally and theoretically. Two isomers were observed by experiment: The first isomer corresponds to the lowest-energy isomer in the calculations, absorbing at ~350 nm and protonated on the C3 atom of the pyrrole ring. According to our calculations, the absorptions of the other isomers protonated on carbon atoms (C2, C4, C5, C6, and C7) are in the visible region. Indeed, the absorption of the second observed isomer starts at 488 nm an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 48 publications
5
89
0
Order By: Relevance
“…The low lying active vibrational modes 28 Figure 6. Comparison among the photofragmentation spectra of protonated quinoline (QH + ), isoquinoline (iQH + ) and naphthalene (NphH + ) in the vicinity of the S 1 S 0 band origin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low lying active vibrational modes 28 Figure 6. Comparison among the photofragmentation spectra of protonated quinoline (QH + ), isoquinoline (iQH + ) and naphthalene (NphH + ) in the vicinity of the S 1 S 0 band origin.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary do not differ much in energy from those of its structural isomer. In-plane iQH + vibrational modes [28][29][30][31][32][33] are again active in S 1 , the same three modes, exp = 588 cm 1 ( 30 , symmetrical ring deformation), exp = 486 cm 1 ( 31 , symmetrical breathing) and exp = 467 cm 1 ( 32 , 14 nonsymmetrical breathing) prevailing. The modes [30][31][32] …”
Section: Calculationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Clear vibronically resolved two-photon photofragmentation spectra of the protonated indole cation were recently reported by Jouvet and coworkers. 49 Fig. 2b presents the low energy band PD mass spectrum acquired also at = 340 nm for the isoquinolineH + isomer.…”
Section: Computationalmentioning
confidence: 99%
“…[46][47][48][49][50] Recent high-resolution experiments showed that rotational temperatures can reach down to 20-35 K (see Section VII C), while the trap is operated at 4.4 K. The biggest advantage of the 3D Paul trap is its ease of operation and its suitability for extracting ions for subsequent time-of-flight mass analyses. A number of cryogenic Paul traps have been built recently to conduct spectroscopy on cold ions, [71][72][73][74] in particular, Johnson and co-workers have developed it into a powerful cryogenic ion spectroscopy technique via H 2 tagging. [28][29][30] The current ESI Paul trap system at Brown University has been significantly improved over the first design.…”
Section: B the Cryogenic Paul Trapmentioning
confidence: 99%